2017
DOI: 10.1111/1759-3441.12167
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies on Innovation Performance in the Manufacturing and Service Sectors Since 1995: A Systematic Review

Abstract: This paper reviews the literature on firm innovation performance from 1995 until 2016. The empirical literature on this topic has been growing continuously over the last few decades. Previous research has investigated the explanatory variables and their impact on firm innovativeness separately. The present systematic review brings together all explanatory variables explored in the literature, classified according to their direction of causality and impact on innovation. These are represented in a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 158 publications
(410 reference statements)
2
18
0
Order By: Relevance
“…Prior studies investigating the relationship between innovation type and business performance in different industries were examined to identify keywords operationalized for search presented in the literature review (Klewitz & Hansen, 2014;Kolluru & Mukhopadhaya, 2017;Sethibe & Steyn, 2015). Similarly, keywords for the search related to innovation were deduced from OECD definition of innovation type.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies investigating the relationship between innovation type and business performance in different industries were examined to identify keywords operationalized for search presented in the literature review (Klewitz & Hansen, 2014;Kolluru & Mukhopadhaya, 2017;Sethibe & Steyn, 2015). Similarly, keywords for the search related to innovation were deduced from OECD definition of innovation type.…”
Section: Search Strategymentioning
confidence: 99%
“…Furthermore, the latest review studies were concentrated on the innovation-performance relationship regardless of the industry sector (Ndesaulwa & Kikula, 2016;Shouyu, 2017), or focused only on firms in the same industry where firms tend to act similarly (e.g. manufacturing or, service) (Becheikh, Landry, & Amara, 2006;Kolluru & Mukhopadhaya, 2017;Rubera & Kirca, 2012) instead of comparing industrial sectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, Damanpour and Aravind asserted that the relationship between innovation and performance had not been explained fully and more empirical studies were needed to explain it [14]. Though, most of the literature concluded that innovation was positively related to performance [15], [16], 17].…”
Section: Innovationmentioning
confidence: 99%
“…Does this also apply to other types of service industries? Thirdly, it is acknowledged that firms across industries struggle with the challenges related to sustainable value creation (Kolluru & Mukhopadhaya, 2017;Raisch, Birkinshaw, Probst, & Tushman, 2009). This study provides insight into the prevalence of strategies that firms within different industries enact to balance exploration and exploitation.…”
Section: Introductionmentioning
confidence: 94%
“…We controlled for firm size as it has been found to influence firm performance (Hannan & Freeman, 1989;Kolluru & Mukhopadhaya, 2017). Firm size is measured by the natural logarithm of total assets in 2006 (Franck et al, 2010;Hamadi & Heinen, 2015).…”
Section: Control Variablesmentioning
confidence: 99%